PENGARUH INOVASI MENU, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DI MCD DARMO SURABAYA - Chrisna Dwi Setya Sutanto; Istiono Istiono (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine and analyze the influence of menu innovation, service quality, and price perception on customer satisfaction at McDonald's Darmo Surabaya. Facing competition in the fast-food industry, it is crucial for companies to understand the factors that can increase customer satisfaction. The three independent variables studied menu innovation, service quality, and price perception are considered important elements influencing consumer decisions and experiences.This study used a quantitative approach with a survey method. Data were obtained through questionnaires from 100 respondents and analyzed using multiple linear regression with SPSS version 26. The F-test results indicated that menu innovation, service quality, and price perception simultaneously had a significant effect on customer satisfaction. The calculated F-value of 75.599 was greater than the F-table value of 2.70, with a significance level of 0.000. Partially, the t-test results indicate that these three variables also significantly influence customer satisfaction, with calculated t-values of 2.685 (menu innovation), 4.603 (service quality), and 2.223 (price perception), all exceeding the t-table value of 1.985 and significantly below 0.05. The adjusted R² value of 0.693 indicates that 69.3% of the variation in customer satisfaction is explained by these three variables.The results of this study conclude that to maintain and improve customer satisfaction, McDonald's Darmo Surabaya needs to continue innovating its menu, improving service quality, and maintaining price perceptions that align with customer perceived value.